What is psychotherapy today? Overview of psychotherapeutic concepts - Adam Pawlak; Agnieszka Kacprzyk-Straszak (Kazimierz Wielki University, 2020)
Psychotherapy is a method of treatment that uses a variety of skills based on theoretical knowledge to help the patient, his well-being and mental health. Medicine and psychotherapy can complement each other effectively. The selection of the most effective treatment method for a particular case is possible by familiarizing yourself with the basic psychotherapeutic trends. The following psychotherapeutic concepts are discussed in the paper: psychoanalytical behavioral - cognitive and humanistic.